Bahasa Inggris - Yunil Hamri, Muhammad Syauqi; Albahi, Muhammad; Martias, Dony (Universitas Islam Negeri Alauddin Makassar, 2025)
This study analyzes market reactions to stock split announcements for sharia-compliant stocks on the Indonesia Stock Exchange (IDX) for the 2025 period. Event-based corporate action studies on the Indonesian sharia-compliant stock segment are still limited, creating a research gap regarding the effectiveness of nominal signals in boosting trading liquidity, particularly when measured using Trading Volume Activity (TVA). The study employed an event study approach with a 10-day event window and a Paired Sample T-Test on paired data (pre–post event) to detect changes in average TVA. The sample consisted of five sharia-compliant issuers (n=5). The results showed an increase in average TVA from 0.00219 to 0.00311, but was not statistically significant (p=0.376>0.05; t=–0.996; 95% CI: –0.00349 to 0.00165). These findings confirm that the sharia-compliant stock market does not react strongly to short-term volume-based nominal stock split signals, challenging the general assumption of signaling theory in the sharia context. This novel research provides the latest empirical evidence that Islamic investors, including institutional investors, are more fundamentally oriented. Policy implications emphasize the need to strengthen literacy and disclosure standards by the Financial Services Authority (OJK) and IDX Syariah, as well as issuers' communication strategies for corporate actions.